2000
DOI: 10.1089/152581600319469
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Biologic Significance of Abnormal Lipid Profiles in Patients with Myelodysplastic Syndromes

Abstract: Serum lipid profiles were obtained in 108 patients with myelodysplastic syndrome (MDS) and compared to 28 healthy volunteers. Serum cholesterol and low-density and high-density lipoproteins (LDL and HDL) were found to be significantly lower in MDS patients than in normals (p = 0.0001, 0.0038 and 0.037, respectively). This difference was significant for all MDS categories. Serum cholesterol and HDL were negatively related to biopsy cellularity (p = 0.001 and 0.0001, respectively), and serum triglycerides were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Hypocholesterolemia has been described in various hematological disorders [1], including thalassemia major [2], thalassemia intermediate [3], sickle cell disease [4], glucose-6-phosphate dehydrogenase (G6PD) deficiency [5], spherocytosis [6], aplastic anemia [7], and myelodysplastic syndrome [8]. The pathophysiology of the hypocholesterolemia in these settings remains obscure, although several mechanisms have been proposed: plasma dilution due to anemia, increased cholesterol requirement associated with erythroid hyperplasia, macrophage system activation with cytokine release, increased cholesterol uptake by the reticuloendotial system, and liver injury secondary to iron overload [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hypocholesterolemia has been described in various hematological disorders [1], including thalassemia major [2], thalassemia intermediate [3], sickle cell disease [4], glucose-6-phosphate dehydrogenase (G6PD) deficiency [5], spherocytosis [6], aplastic anemia [7], and myelodysplastic syndrome [8]. The pathophysiology of the hypocholesterolemia in these settings remains obscure, although several mechanisms have been proposed: plasma dilution due to anemia, increased cholesterol requirement associated with erythroid hyperplasia, macrophage system activation with cytokine release, increased cholesterol uptake by the reticuloendotial system, and liver injury secondary to iron overload [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids, an integral part of biomembrane, are essential for several biological functions including normal cell growth and division, as well as for cellular proliferation (Allampallam et al, 2000). Although abnormalities of lipids have been implicated in the pathogenesis of cardiovascular diseases, altered levels of lipids and lipoproteins in circulation have also been found to be associated with the etiopathogenesis of several cancers Kolanjiappan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia can induce the production of reactive oxygen species (ROS), such as superoxide anion, via enzymes including the oxidase for the reduced form of nicotinamide adenine dinucleotide phosphate (NADPH) and xanthine oxidase, and other sources of ROS from mitochondria [4]. Some investigators have reported an association between levels of plasma or serum lipids and lipoproteins, and various types of cancers [5][6][7]. Individual susceptibility to cancer can result from several host factors, especially differences in the activity of xenobioticmetabolizing enzymes [8].…”
Section: P Tanaviyutpakdee Et Almentioning
confidence: 99%